Noninvasive functional testing in ANOCA: hyperventilation-exercise study for spasm (SESPASM). (14th October 2021) - Dedic, S; Boskovic, N; Giga, V; Nedeljkovic, I; Tesic, M; Jovanovic, I; Aleksandric, S; Beleslin, B; Picano, E; Djordjevic Dikic, A
Abstract: Introduction: In patients with angina and no obstructive coronary artery disease (ANOCA), different mechanisms of ischaemia, epicardial spasm, microvascular spasm, and impaired microvascular dilatation frequently coexist. The aim was to assess CFVR changes during coronary vasoconstrictor and vasodilator stimuli in patients with ANOCA. Methods: In a prospective single center study, we enrolled 29 ANOCA patients (age 59.6±11 years, 27 females) with previously normal angiograms. All underwent SE testing with hyperventilation (HYP, respiratory rate of 30 per min for 5') followed by supine bicycle exercise (HYP+EXE); and adenosine CFV evaluation (ADO 140 mcg/kg in 1 min) on the other day. Coronary flow velocity (CFV) was assessed in distal LAD by Transthoracic Doppler echocardiography. The ratio of peak/rest changes of CFV during HYP in LAD was taken as an index of vasoconstriction, and CFV reserve was evaluated after EXE. An abnormal response to HYP was a CFV ratio <1.0 (vasoconstrictor response). An abnormal response to ADO was a CFV reserve <2.0 (blunted vasodilatory response). CFVR at peak HYP+ EXE was an indicator of endothelial dependent vasodilatation. Results: The double product increased during HYP, in comparison to rest (13213 vs 10517, p<0.01), and further increased with EXE (23387 vs HYP, p<0.001). Chest pain or dyspnea were present in 4/29 pts during HYP, and in 7/29 patients during HYP+EXE (13.8% vs 24.1%, p=0.001). ST segment depression (≥1mm) was present in 7/29 patients during HYP, and 14/29 during HYP+EXE (24.13% vs 48.3%, p<0.01). Five patients (17%) showed regional wall motion abnormalities with HYP+EXE. CFVR response was abnormal in 19/29 (65%) patients during HYP+EXE, and abnormal for vasoconstriction during HYP in 13 (44%). Vasodilation during ADO was preserved in all patients.There was significant difference between CFVR response during HYP+EXE and ADO (1.9±0.35 vs 2.47±0.42 respectively, p<0.01), and between CFVR HYP and ADO (1.28±0.29 vs 2.47±0.42, p<0.001). Conclusion: In patients with ANOCA, HYP+EXE is a more powerful ischemic stress than HYP alone. In over one-half of patients HYP+EXE unmasks abnormalities in CFVR response and/or regional wall motion, likely unmasking the underlying endothelium dependent microcirculatory dysfunction with enhanced vasoconstriction in 44% of the patients and mixed vasoconstriction and reduced relaxation in 65%. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University Clinical Centre of Serbia, Faculty of Medicine